An overview of the neuropathology of neurodegenerative diseases - Lashley, Tammaryn (Henry Stewart Talks, 2014)
Overview of the underlying pathology seen in different neurodegenerative diseases including Alzheimer’s disease, Dementia with Lewy bodies, The heterogeneous group of frontotemporal dementias and the hereditary familial British and Danish dementias., The pathological proteins for each disease are discussed and the types of pathological lesions formed.